Color Stability, Surface Roughness, and Microhardness of Resin-Based Composites After Immersion in Beverages Commonly Consumed by Children or Accelerated Artificial Aging - Mariana Oliveira Daltoé; Eduardo José Soares; Rocio Geng Vivanco; Raquel Assed Bezerra da Silva Segato; Patrícia Gatón-Hernández; Paulo Nelson-Filho; Fernanda de Carvalho Panzeri Pires-de-Souza; Léa Assed Bezerra da Silva (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To evaluate the color stability, surface roughness, and microhardness of resin-based composites (RBCs) after accelerated artificial aging (AAA) or immersion in beverages consumed by children. Material and Methods: Seventy specimens were prepared from each RBC (Z350-Z350, SS-Spectra Smart, AF-Admira Fusion, and EA-Estelite Asteria). Initial color, ∆E00, surface roughness, ∆Ra, and microhardness, ∆KHN readings were done. Specimens were separated into five groups (n=14): AAA (300 hours) and immersion (30 minutes daily/30 days) in Coca-Cola (CC), Grape juice (GJ), Chocolate milk (CM), or distilled water (DW). After the final readings, color and microhardness data were analyzed using two-way ANOVA, Tukey, and surface roughness by Kruskal-Wallis and Dunn's test. Results: SS exhibited the most significant color change in AAA, which differed from CC and GJ; the minor change occurred after CM and DW, which were distinct from each other. AF did not show a difference between the treatments. All RBCs exhibited a decrease in microhardness, except for SS, after AAA and EA in CC and DW. There was no difference in the surface roughness after treatments, except for AAA, which presented a minor change for Z350 and AF, differing from the other treatments. Conclusion: The beverages didn’t alter the surface roughness but decreased the microhardness of the RBCs, except for CC, which increased the microhardness of EA.